Multiplatform-Based Digital Market Designs as Marketing and Sales Media of MSME Products in Pleret Village - Taufiq Kamal; Zulfatun Ruscitasari; Yana Hendriana; Wahma Ravenna Rafail (Jurusan Teknik Informatika, 2021)
Purpose : This study aims to design a multiplatform-based digital market to help rural MSMEs (Micro, Small, Medium Enterprises) market and sell their products in order to increase the competitiveness of MSMEs.Design/methodology/approach : The design of the digital platform of Ngedolke.com used a design thinking strategy. This study used the black box method to test the functional suitability of the developed application.Findings/result : This study produces an analysis and system design that is used to develop the digital platform of Ngedolke.com. Thus, it can be used to develop the system further.Originality/value/state of the art : The difference between this study and previous studies lies in the use of system design of a design thinking strategy. Besides, the technology used is multiplatform-based.